Chapter 5 La informalización del discurso público en X1 (antiguo Twitter) - Pérez-Sabater, Carmen (Taylor & Francis, 2024)
La informalización del discurso digital público is an innovative volume which examines different communicative practices which take place on social media and justifies the shift towards more informal/oral styles of public communication in English and Spanish. The book takes a first step in understanding and analysing how the use of code-switching, language preference, and graphicons contribute to the public image of institutions, politicians and celebrities, as well as how the aforementioned strategies fit into the negotiation of the norms and identities of public communities on social media platforms. Offering an updated approach to studying digital discourse in public contexts, it is the first of its kind written in Spanish. The volume focuses on the characteristic linguistic features associated with digital communication and informal oral writing styles, such as reduplication of vowels, consonants, acronyms, and shortenings, code-switching and language preference, and the insertion of multimodal and graphical elements. A comprehensive and unique volume, La informalización del discurso digital público is ideal for researchers and postgraduate students interested in digital discourse, sociolinguistics, and media studies.